Compensation committee gender diversity and CEO pay-performance link: Evidence from Australia, China, and Pakistan - Umaal Ahmed Khan; Khalid Waleed; Muhammad Nouman; Sobia Khurram (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
In this study, we examine the crucial question whether the presence of female directors in the compensation committee (CC) improves the committee objectivity (i.e., paying executives for performance) in context of three countries namely Australia, China, and Pakistan. Using the data of public listed companies of these countries we find mixed results. Our results suggest that firms with gender-diverse CC strengthen the CEO payperformance link only in Chinese listed firms. Our findings remain consistent even after controlling for possible issue of endogeneity. Overall, this paper highlights the diversity practices of China, Australia and Pakistan and provides empirical evidence to corporate world and regulatory bodies.
Keywords: 330; gender diversity; compensation committee; female executives; CEO pay; pay-performance link